Effects of sildenafil on nanostructural and nanomechanical changes in mitochondria in an ischaemia‐reperfusion rat model. (October 2014) - Lee, Kyung Hye; Kwon, Sung Jin; Woo, Jong‐Shin; Lee, Gi‐Ja; Lee, So‐Ra; Jang, Hyun‐Hee; Kim, Hyun Soo; Kim, Jung Wook; Park, Hun Kuk; Cho, Kyu Seok; Kim, Weon
Summary Sildenafil exerts cardioprotective effects by activating the opening of mitochondrial ATP‐sensitive potassium channels to attenuate ischaemia–reperfusion (IR) injury. In the present study, we used atomic force microscopy (AFM) to investigate changes in mitochondrial morphology and properties to assess sildenafil‐mediated cardioprotection in a rat myocardial infarction model. To investigate the cardioprotective effects of sildenafil, we used an in vivo Sprague‐Dawley rat model of IR. Rats were randomly divided into three groups: (i) sham‐operated rats (control; n = 5); (ii) IR‐injured rats treated with vehicle (normal saline; IR; n = 10); and (iii) IR‐injured rats treated with 0.75 mg/kg, i.p., sildenafil (IR + Sil; n = 10). Morphological and mechanical changes to mitochondria were analysed by AFM. Infarct areas were significantly reduced in sildenafil‐treated rats (7.8 ± 3.9% vs 20.4 ± 7.0% in the sildenafil‐treated and untreated IR groups, respectively; relative reduction 62%; P < 0.001). Analysis of mitochondria by AFM showed that IR injury significantly increased the areas of isolated mitochondria compared with control (24 150 ± 18 289 vs 1495 ± 1139 nm2, respectively; P < 0.001), indicative of mitochondrial swelling. Pretreatment with sildenafil before IR injury reduced the mitochondrial areas (7428 ± 3682 nm2; P < 0.001; relative reduction 69.2% compared with the IR group) and ameliorated the adhesion force of mitochondrial surfaces. Together, these results suggest that sildenafil has cardioprotective effects against IR injury in a rat model by improving the morphological and mechanical characteristics of mitochondria.